2019
DOI: 10.1002/hep.30315
|View full text |Cite
|
Sign up to set email alerts
|

Colder Weather and Fewer Sunlight Hours Increase Alcohol Consumption and Alcoholic Cirrhosis Worldwide

Abstract: Risk of alcoholic cirrhosis is determined by genetic and environmental factors. We aimed to investigate if climate has a causal effect on alcohol consumption and its weight on alcoholic cirrhosis. We collected extensive data from 193 sovereign countries as well as 50 states and 3,144 counties in the United States. Data sources included World Health Organization, World Meteorological Organization, and the Institute on Health Metrics and Evaluation. Climate parameters comprised Koppen-Geiger classification, aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
1
26
0
2
Order By: Relevance
“…I read with interest regarding the influence of colder weather and fewer sunlight hours on the increase in alcohol consumption and alcoholic cirrhosis. (1) The study of a global cohort including 193 countries showed that colder climates may play a causal role on alcohol-attributable fraction (AAF) of cirrhosis mediated by alcohol consumption. Although it may hold true in many countries, the situation in Taiwan appears to be opposite to this conclusion.…”
Section: Letter To the Editor: Can Colder Weather And Fewer Sunlight mentioning
confidence: 99%
See 3 more Smart Citations
“…I read with interest regarding the influence of colder weather and fewer sunlight hours on the increase in alcohol consumption and alcoholic cirrhosis. (1) The study of a global cohort including 193 countries showed that colder climates may play a causal role on alcohol-attributable fraction (AAF) of cirrhosis mediated by alcohol consumption. Although it may hold true in many countries, the situation in Taiwan appears to be opposite to this conclusion.…”
Section: Letter To the Editor: Can Colder Weather And Fewer Sunlight mentioning
confidence: 99%
“…We have read with interest the article by Dumortier et al reporting that patients with hereditary hemorrhagic telangiectasia (HHT) have a high radiological recurrence rate after liver transplantation (LT) with an estimated cumulative risk of 47.9% at 15 years, although clinical consequences in terms of symptomatic liver disease are unknown. (1) The immunosuppressant regimen used in these patients was based in calcineurin inhibitors (tacrolimus and ciclosporin) in addition to mycophenolate mofetil when necessary. The authors suggest the possible role of antiangiogenic medications, such as bevacizumab, as adjuvant therapy to LT when radiological recurrent disease appears.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Hepatology , Ventura‐Cots et al present their study arguing that colder weather and fewer sunlight hours increase alcohol consumption and thus cause alcoholic cirrhosis . “Causality” is a key concept for this study.…”
mentioning
confidence: 94%